2010
DOI: 10.1128/ec.00020-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lysine Biosynthesis as an Antifungal Drug Target: Biochemical Characterization of Aspergillus fumigatus Homocitrate Synthase and Virulence Studies

Abstract: Aspergillus fumigatus is the main cause of severe invasive aspergillosis. To combat this life-threatening infection, only limited numbers of antifungals are available. The fungal ␣-aminoadipate pathway, which is essential for lysine biosynthesis, has been suggested as a potential antifungal drug target. Here we reanalyzed the role of this pathway for establishment of invasive aspergillosis in murine models. We selected the first pathway-specific enzyme, homocitrate synthase (HcsA), for biochemical characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 68 publications
1
63
0
Order By: Relevance
“…In this regard, our results indicated that the decrease in the 2-OG supply may be a suitable strategy for development of drugs that target the a-AAP in fungi, although this would be successful only for fungal pathogens that lack high-affinity Lys uptake systems [39]. Our findings also suggested that enhancement of both the 2-OG supply and Lys20 activity may be appropriate strategies to increase the synthesis of Lys free .…”
Section: Biotechnological Implications Of the Flux-control Distributimentioning
confidence: 56%
“…In this regard, our results indicated that the decrease in the 2-OG supply may be a suitable strategy for development of drugs that target the a-AAP in fungi, although this would be successful only for fungal pathogens that lack high-affinity Lys uptake systems [39]. Our findings also suggested that enhancement of both the 2-OG supply and Lys20 activity may be appropriate strategies to increase the synthesis of Lys free .…”
Section: Biotechnological Implications Of the Flux-control Distributimentioning
confidence: 56%
“…The strongly attenuated virulence of Δ riboB and Δ panA mutants in all tested virulence models demonstrates that both riboflavin and pantothenic acid biosynthesis are not only essential for invasion (intranasal infection model) but also during dissemination (intravenous infection model). In contrast, lysine biosynthesis was previously found to be essential exclusively for invasion but not during dissemination [10,11]. Virulence analysis of auxotrophs was previously tested in the closely related Aspergillus nidulans during the 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…Using a combination of comparative genomics, transcriptomics and metabolic flux analysis, we recently identified 64 fungal-specific targets including metabolic enzymes participating in amino acid, lipid and vitamin biosynthesis [8]. Of these, 18 targets have already been validated in the literature, including enzymes participating in the biosynthesis of aromatic amino acids [9], lysine [10,11], histidine [12] and cysteine/methionine [13] and in the biosynthesis of lipids, including phospholipids [14], fatty acids [6] and oxylipins [15]. However, the assessment of fungal-specific targets in the vitamin biosynthesis pathways and their importance during infection has not been well established.…”
Section: Introductionmentioning
confidence: 99%
“…The observations of Schöbel and colleagues revealed that an A. fumigatus lysine auxotroph is able to germinate and grow on partially digested proteinaceous substrates [10], which is also the case for an A. fumigatus cysteine auxotroph [20]; moreover the mutant is fully virulent in a disseminated disease model. These observations highlight two critical caveats of targeting amino acid biosynthesis.…”
Section: Perspectives For Drug Developmentmentioning
confidence: 99%
“…For example, none of the non-essential amino acid biosynthetic gene products required for Cryptococcus pathogenicity (detailed below) have thus far been additionally tested in systemic or CSF persistence models (Table 1). For studies of Aspergillus fumigatus several amino acid biosynthetic gene products have been more rigorously addressed, a pivotal study being that of a homocitrate synthase enzyme (HscA), required as the first pathway-specific step (Figure 1) of the lysine biosynthetic α-aminoadipate pathway [10]. Although an HscA null mutant was found to be auxotrophic for lysine biosynthesis, in vitro, and unable to undergo spore germination in media containing unhydrolysed proteins, significant growth of the mutant was observed on blood agar and serum-containing growth media.…”
Section: Niche-specific Requirements For Fungal Amino Acid Biosynthesmentioning
confidence: 99%